An Analysis of the Influence of Abbasid Dynasty Economic Practices on Indonesia's Economic Development - Sindy Marchelia Putri; Muh. Syaukin Muttaqin; Nurlailah Nurlailah; Susilowati Susilowati (Journal of Business Improvement, 2025)
The Abbasid Dynasty is regarded as one of the most prosperous dynasties in history due to significant advancements across various sectors. One of the most prominent was the rapid development of the economic sector, driven by the policies enacted by the reigning caliphs, which brought the Abbasid economy to its peak. Indonesia, which shares similarities in human resources and its vast territory, has the potential to improve its economy amidst the current challenges. This research aims to examine which economic policies from the Abbasid era could be adapted to the contemporary Indonesian economy. The results of this study suggest that the economic policies from the Abbasid period, particularly in agriculture, mining, trade, and taxation, could serve as a reference for addressing Indonesia's current economic challenges. Indonesia possesses similar potential to the Abbasid Dynasty, with both having vast territories and diverse natural resources, as well as relying on taxation as a primary source of state revenue. However, these policies must be adapted to the modern era, considering that Indonesia has a different constitutional foundation than the Abbasid Dynasty